Evaluation and Addition of Waste Water Treatmant Plant Units in West Lombok Regency Hotel - Melinda, Tina; Nurhidayah, Nurhidayah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The development of hotels in Lombok is very drastic, especially in tourist areas. In carrying out their activities, hotels require large amounts of water to meet the needs of guests and employees; besides that, water use in a hotel is also seen in the supporting facilities. Using large amounts of clean water will also produce large quantities of wastewater. This research aims to evaluate wastewater treatment installations at XY Hotel. The method used in this research is a field study followed by an analysis of water quality, process, and output. Based on the evaluation results, the Wastewater Treatment Plant at Hotel Aerobic has capacities of 20 m3/day, 15 m3/day, and 2 m3/day respectively.